Exploring the Anti-inflammatory Components of Gastrodia elata B1 and Their Action Mechanism Based on UPLC-Q-TOF-MS/MS and Network Pharmacology - XU Ningmeng, DONG Shihao, QIN Fen, SHEN Kaize, LI Weilan, HUA Yan, GUO Lei (Shipin Kexue)
This study was carried out in order to explore the anti-inflammatory constituents of the tuber of Gastrodia elata B1 and their mechanisms of action. The petroleum ether extract and its sequential fractions: dichloromethane, ethyl acetate, n-butanol and water-soluble fractions were determined for their active ingredients as well as assessed for their bioactivities. The bioactive ingredients were identified by ultra-high performance liquid chromatography-quadrupole-time of flight-mass spectrometry (UPLC-Q-TOF-MS/MS), and network pharmacology was utilized to predict the potential anti-inflammatory components of the selected fraction and their targets. Furthermore, molecular docking was used to investigate the binding of the potential anti-inflammatory components to the core targets for treating inflammation. The results showed that the ethyl acetate fraction possessed the highest content of bioactive ingredients, with total polyphenol, total flavonoid and polysaccharide contents of (164.69 ± 1.57), (64.81 ± 3.21) and (279.64 ± 3.11) mg/g, respectively. The ethanol extract and its fractions possessed strong in vitro antioxidant and anti-inflammatory activities, among which the ethyl acetate fraction demonstrated the strongest 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging capacity and in vitro anti-inflammatory activity. Correlation analysis showed that the total polyphenol content was significantly (P < 0.05) and highly significantly (P < 0.01) correlated with the half maximal inhibitory concentration (IC50) against DPPH radical and 2,2’-biazobis(3-ethylbenzothiazoline-6-sulfonic acid) cationic radical, with correlation coefficients of −0.587 and −0.873, respectively. The total flavonoid content was significantly (P < 0.05) and highly significantly (P < 0.01) correlated with the IC50 values against NO and the denaturation of bovine serum albumin (BSA), with correlation coefficients of −0.780 and −0.842, respectively. Meanwhile, a total of 164 chemical constituents were identified from the ethyl acetate fraction, and core active ingredients including 5-(5-methoxycarbonyl-5,8a-dimethyl-2-methylidene-3,4,4a,6,7,8-hexahydro-1H-naphthalen-1-yl)-3-methylpentanoic acid, 4,4,8,10,14-pentamethyl-17-(4,5,6-trihydroxy-6-methylheptan-2-yl)-2,5,6,7,9,15-hexahydro-1H-cyclopenta[a]phenanthrene-3,16-dione, and simvastatin and key targets including TP53, SRC, PIK3R1, PIK3CA, and AKT1, which were mainly involved in cancer-related signaling pathways as well as the mitogen-activated protein kinase (MAPK) and cyclic adenosine monophosphate (cAMP) signaling pathways, were obtained by network pharmacology. The results of molecular docking showed that the core active ingredients had good binding activity with the key targets.